UTILIZATION OF MIGRANT WORKERS' REVENUES (REMITTANCE) FOR THE FAMILY ECONOMY - Muhammad Alhada Fuadilah Habib; Unsiyah Anggraeni; Kanita Khoirun Nisa (Journal of Urban Sociology, 2021)
It is undeniable that the high unemployment caused by the imbalance between the number of employment and labor force encourages people to work as migrant workers. In 2016, East Java province was the third largest supplier of migrants in Indonesia and Tulungagung contributed 4,962 inhabitants. This phenomenon is interesting to analyze the utilization of income sent to families in their country. The data used was a primary data conducted by the survey method to 100 respondents. The selection of research sites (sub-district and village) was carried out by simple random sampling while the respondent selection was done by systematic random sampling technique. To deepen the findings of data conducted indepth interviews with 10 informants.  Moreover, the results revealed that remittances were used by the family for daily consumption needs, investment in children’s education, religious ceremonies, home reparation, production activities and others. The authors recommend establishing a "migrant family community" comprising: (1). Rehabilitation of the social culture of migrant workers' families and the provision of "business motivation training", (2). Entrepreneurship training, (3). Development of business networks.Keywords: Migrant Workers, Remittances Use, Welfare